PENGARUH STRUKTUR KEPEMILIKAN, STRUKTUR MODAL, PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019 – 2021 - Ariza Khoirun Nanda; Shadrina Hazmi (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze the ownership structure, capital structure, sales growth, together and partially to the profitability of manufacturing companies of various industries that are listed on the Indonesia Stock Exchange period 2019-2021. Sampling techniques in this study using Purposive Sampling and obtained 46 manufacturing companies of various industries that are listed on the Indonesia Stock Exchange according to the research criteria. The test of the classical assumption testing of this research is normally distributed and produces a free regression model of multicolinearity, heteroscedasticity, autocorrelation so that it can meet the requirements to test multiple linear regression analysis. The results of this study aoda that: (1) ownership structure measured by institutional ownership has a significant negative effect on profitability, (2) the capital structure measured by DER has no effect on profitability, (3) sales growth has a positive effect on profitability, (4) ownership structure, capital structure, sales growth together with a significant effect on profitability.